A Survey of the Phaenocarpa Förster species of the Carpathian Basin, Central Europe (Hymenoptera, Braconidae: Alysiinae). - Papp, Jenö (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The author, having revised from the taxonomical viewpoint the Aphaereta Förster species found in the Carpathian Basin (Central Europe) now presents his new essay on Phaenocarpa Förster. From the known 43 Palaearctic species 14 have been collected in the Carpathian Basin which are now deposited in the Hungarian Museum of Natural History, Budapest, in all 153 specimens. Out of the species 3 are new to science, and 7 are new to the fauna of the Carpathian Basin These numbers, of course, especially the new records to the Carpathian Basin, will increase as scientific research progresses. The following species are known so far from the Carpathian Basin: Phaenocarpa angustiptera sp.n. Ph. collaris sp. n., Ph. conspurcator (Haliday), Ph. eugenia (Haliday), Ph. eunice (Haliday), Ph. flavipes (Haliday), Ph. laticellula sp. n., Ph. livida (Haliday), Ph. nitida Thomson, Ph. picinervis (Haliday), Ph. pratellae (Curtis), Ph. pullata (Haliday), Ph. ruficeps (Nus), Ph. tabida (Nees). - This essay contains a characterization of the genus Phaenocarpa, a key to the species, a detailed description of each species, their distribution and a list of the localities in the Carpathian Basin (Czechoslovakia, Hungary, Roumania, and Yugoslavia). By examining types the author found that Phaenocarpa arctica Thomson and Ph. tatrica Niezabietowski are synonym with Ph. conspurcator (Haliday ), and he describes the male of Ph. nitida Thomson which was unknown so far. Nomenclatural Acts angustiptera Papp, 1968 (Phaenocarpa), spec. n. arctica Thomson, 1895 (Phaenocarpa), syn. n. of Phaenocarpa conspurcator (Haliday, 1838) collaris Papp, 1968 (Phaenocarpa), spec. n. laticellula Papp, 1968 (Phaenocarpa), spec. n.